The philosophy of learning and listening in traditional classroom and online learning approaches - Hassan, Aminuddin; Zainal Abiddin, Norhasni; Sim, Kuan Yew (Canadian Center of Science and Education, 2014)
It is important to consider the concepts of traditional classroom and online learning in evaluating effective learning and listening conducted in higher learning institutions. To reach the depth of both concepts, one should understand them in the philosophical point of view. Both traditional classroom and online learning play a role in the learning process. It was investigated by many researchers before and important findings had been revealed. Both play different roles. There are researchers who came out with blended learning as the solution. However, many other factors need to be considered. This study has defined several objectives to investigate the type of learning that can provide high achievement within the students and to determine whether there is any significant difference in metacognitive awareness listening strategies students used in learning listening online and learning listening in a traditional classroom. This study was conducted in Universiti Sains Islam Malaysia (USIM), a local university in Negeri Sembilan. This university is located in Nilai, Negeri Sembilan. 44 students were selected (22 in control group, 22 in experimental group) from the Syariah and Law Faculty as participants of the research. From the pre-test, the student’s level of proficiency was the same. After determining on what type of instruments and data analysis procedure to be used, the researcher compared the data using t-test. In listening strategies, based on the findings, there is no significant difference between two groups of approach. The students use the same strategy either online classroom or traditional classroom. It differs on the type of strategy used, but the frequency of applying the strategy between two groups is the same. Because the result showed that traditional classroom performed better result than online, it might have been something wrong with the courseware used by the teacher. The lack of instruction provided by the teacher might be why the students in online learning could not perform in the listening task.